Professional Identity in Chilean Translation Trainees: Initial Positioning, Perceptions and Valuations [Identidad Profesional en Estudiantes de Traducción Chilenos: Posicionamiento, Percepciones y Valoraciones Iniciales] - Basaure-Cabero, R; Singer-Contreras, N (Universidad de Antioquia, 2020)
Affective development in translator education is an issue that has been under-researched, particularly the development of professional identity among translators in training. This article presents a phenomenological study on how translator trainees develop their professional identity. This study examines their narratives concerning their self-descriptions and perceptions on professional translator and their training at the start of this study-i.e. March 2018. To do this, semi structured interviews were conducted with a group of nine third-year translation trainees in an undergraduate Translation program in Chile. Results show that students (a) describe themselves as shy, insecure individuals, who find it difficult to socialise; (b) present an idealised vision of the professional translator, which is misaligned with their self-perceptions; (c) experience an emotional conflict between the fear to alterity and their agency to fulfil their academic and personal commitments; and (d) prize the training received so far. It is concluded that these elements make up for a valuable input to plan translation course units at later stages of the program. © 2020, Universidad de Antioquia.